HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI DENGAN PERILAKU SEKSUAL BERESIKO PADA REMAJA SMA DI DESA MOJOAGUNG KAB.PATI: KESEHATAN REPRODUKSI - Wahyuni, Sri; Parmila Hesti S, Naomi; Mahanani, Annisah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
This study aims to analyze the relationship between reproductive health knowledge and risky sexual behavior among high school adolescents in Banjarmasin City. This cross-sectional research involved 256 students aged 15-18 years selected through stratified random sampling from five public high schools. Data were collected using validated questionnaires for reproductive health knowledge and risky sexual behavior. Data analysis used chi-square test and multivariate logistic regression. Results showed that 64.8% of respondents had adequate reproductive health knowledge, while 35.2% had inadequate knowledge. Regarding risky sexual behavior, 23.4% of respondents reported engaging in at least one form of risky sexual behavior. Statistical analysis revealed a significant relationship between reproductive health knowledge and risky sexual behavior (p=0.001; OR=3.28; 95% CI: 1.92-5.61), indicating that adolescents with inadequate knowledge were 3.28 times more likely to engage in risky sexual behavior. The relationship remained significant after controlling for variables such as age, gender, parental communication, peer influence, and access to information. The study concludes that improving reproductive health knowledge among adolescents is crucial in reducing risky sexual behavior. Recommendations include strengthening reproductive health education in schools, enhancing parent-adolescent communication, and developing comprehensive reproductive health programs tailored to adolescents' needs.